Determination of Effective Schools in Undergraduate School State Islamic University of North Sumatera - Indra Jaya (BIRCU, 2019)
Effective schools at the undergraduate level are very decisive educational institutions in producing future generations of scholars. Several strong factors can change tertiary institutions, such as undergraduate schools at the North Sumatra State Islamic University into effective schools. These factors are a commitment that is owned by the organizers, the organizer's trust, interpersonal communication, leadership and organizational culture that is in it.